Study of Socio Demographic Predictors of Adherence of Anti Retroviral Therapy (ART) among HIV Positive Patients – A Case Control Study - Modi, Bhautik P; Gharat, Vaibhav; Patel, Prakash B; Nayak, Sunil; Prasad, Rachna; Bansal, R K (National Journal of Community Medicine, 2017)
Introduction: After starting free Anti Retroviral Therapy (ART) in India, challenge has changed from gaining access to taking the treatment correctly and consistently in order to realize the rewards of improved health status, and reduced morbidity and mortality from HIV. This study was aimed to identify of socio-demographic risk factors responsible for non-adherence to ART. Methodology: This Case Control Study was conducted at ART centre where all patients with poor adherence percentage i.e. ≤ 95% of Treatment Adherence were denoted as ‘Case’ and good adherence percentage i.e. > 95% of Treatment Adherence were denoted as ‘Control’. The ‘Pill Count method’ was used to measure the adherence level. Results: Mean age of 104 cases and 208 unmatched controls was 36.29 years and 39.21 years respectively (p <0.05). Females were more common among cases than controls. Total 15.4% of cases and 7.7% of controls were from the rural area (OR: 2.18 (1.04 - 4.56) and p-Value < 0.05). Post-test counselling was not done in 10% of cases and 4% of controls. [OR: 2.66 (1.02 - 6.96)& p-Value < 0.05]. Conclusion: Poor adherence was more in younger, female, rural residence, low family income, disclosure of HIV positive status and patients undergone post test counselling.